Social relationships of women with cervical cancer in chemotherapy treatment (Research, Society and Development, 2020)
The social relations are a number of factors that influence the vision that each individual has of certain fact. Deep in the context of women with cancer cervix, the social relations will be of high relevance to detect the understanding and behavior of women that experience it and how these relations can step in the therapeutic of those patients during this process. The main is to investigate the social relations of cancer of the cervix for women in chemical treatment. It’s about an integrative review of quality approach held in September of 2020, through the database of Virtual Health Library (VHL). Social relationship were affected during and after the chemotherapy treatment because the side-effects spawned mainly in the family enviroment, specifically in the partner. See a table 3 the analyzed patients experienced discomfort´s moments and fellings proven in the form of physical and psychological symptoms; however, it was noticeable behind the data analysis that in the marjority of the affected public, the obtained support in front of the desease confront´s process is substancial for the positive result of the treatment and improvement in the social relation. This way, it was noticeable that the discussed issue is little explored, with the need of a study elaboration focused at the social\family intervention of women in the cancer´s confront, furthermore the nurse´s care will be of great relevance in the development of a strategy that improves the quality of life of women and the enviroment she is at.